Laser-ablation rates measured using x-ray laser transmission - Edwards, M H; Whittaker, D S; Tallents, G J; Mistry, P; Pert, G J; Rus, B; Mocek, T; Kozlová, M; Polan, J; Praeg, A; Stupka, M; Homer, P (Physical review letters, 2007)
The rate of laser ablation at irradiances of approximately 2 x 10{14} W cm{-2} of solid iron has been measured using the transmission of a neonlike zinc x-ray laser at 21.2 nm through thin iron targets. Ablated iron becomes transparent to the x-ray laser flux, enabling the thickness of unablated material and hence the rate of ablation to be measured from time resolved x-ray laser transmission.